Response to dietary supplementation of L-glutamine and L-glutamate in broiler chickens raised at different stocking densities under the hot, humid tropical conditions - Shakeri, Majid; Idrus, Zulkifli; Farjam, Abdoreza Soleimani; Amir, Anna Aryani; Kumari, S.; Abdullah, Faez Firdaus Jesse (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
This research was conducted to evaluate the effect of AminoGutTM (a mixture of Gln and Glu) 0.5% for first 3 weeks and 6 weeks on performance of broiler chickens stocked at 10 birds/m2 and 15 birds/m2. Supplementing 0.5% AminoGutTM did not affect growth performance and serum acute phase protein (APP) level. The high stocking density impaired growth performance and increased serum APP concentration as compared to the low stocking density.